Diagnosa Penyakit Tanaman Cabai menggunakan Metode Forward Chaining dan Naïve Bayes - Efendi, Riyo; Fauziah, Fauziah; Gunaryati, Aris (KITA Institut, 2021)
The purpose of this research is to design a web-based expert system application to provide information about chili plant diseases and to diagnose the symptoms of diseases that attack chili plants and to provide solutions for appropriate handling methods, which can be accessed anywhere and utilized by the wider community and can speed up the time to deal with diseases that attack chili plants. This study uses the Forward Chaining and Naïve Bayes Methods in order to know the facts/signs of chili disease so that you can get the best quality chili. Based on the results of the discussion and calculation of the web-based expert system for diagnosing chili disease using the Forward Chaining and Naïve Bayes methods, it can be concluded that a simple application it can make it easier for users to diagnose chili disease and find out the causes and solutions. And can find out the total number of all comparisons of the 2 methods.Keywords:Chili disease, Expert System, Forward Chaining, Naïve Bayes.